Increasing Students’ Vocabulary Mastery by Using Pictures at Smp Negeri 2 Tondano - Nelwan, Silvana Mariana; Pelenkahu, Noldy; Hampp, Paula (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2025)
This study set out to investigate whether or not using pictures could increase pupils’ vocabulary mastery. Twenty students in seventh-grade students from SMP Negeri 2 Tondano were chosen for this study for the 2023–2024 academic year. A quantitative research methodology is being applied. In this study, paired sample T-tests and normality tests were employed for data analysis and hypothesis testing. The present study employed a pre-experimental design with a single group pre-test and post-test. This research consisted of three meetings. That amounts to ten aims, and ten numbers translated means twenty numbers. Before beginning treatment, the first researcher administered a pre-test (using photographs). After treatment, the students were given a post-test (using pictures). Tests were utilized as an instrument in the data-gathering process. The study’s findings indicated that using pictures helped students do better on the post-test (87.50) than on the pre-test (62.25). It also implies that utilizing pictures to teach vocabulary benefits pupils in learning more effectively